Development and validation of a problem-solving instrument (multiple-choice questions) for computational thinking among trainee teachers in the Klang Valley, Malaysia - Abdul Hamed, Ahmad Sarji; Wong, Su Luan; Abdul Zani, Mohd Zariat (Asia-Pacific Society for Computers in Education, 2024)
In the 21st century, the integration of computational thinking (CT) into education has become crucial, enhancing students' abilities to address complex problems through systematic and innovative approaches. Malaysia has recognized this need by embedding CT into its national curriculum, emphasizing key components such as abstraction, decomposition, pattern recognition, algorithms, logical reasoning, and evaluation. However, challenges remain in defining CT consistently and assessing its integration effectively, particularly among trainee teachers. This study aims to develop a robust multiple-choice question (MCQ) assessment tool to measure CT skills among trainee teachers in Malaysia. Utilizing a mixed-methods approach, the research begins with qualitative insights from educational technology experts to refine CT definitions and components. This informs the subsequent quantitative phase, involving the development and validation of the MCQ tool. Key objectives include evaluating content validity, difficulty and discrimination indices, and construct validity. The study's outcomes will provide a standardized measure of CT, guiding educational strategies and enhancing teacher training programs to better prepare educators for the digital age. The research underscores the importance of a universal CT assessment tool tailored to Malaysia's educational context, promoting consistent and equitable development of essential 21st-century skills.